2022
DOI: 10.1186/s13287-022-03168-5
|View full text |Cite
|
Sign up to set email alerts
|

Roles of microglia/macrophage and antibody in cell sheet transplantation in the central nervous system

Abstract: Background We previously established a human mesenchymal stem cell (MSC) line that was modified to express trophic factors. Transplanting a cell sheet produced from this line in an amyotrophic lateral sclerosis mouse model showed a beneficial trend for mouse life spans. However, the sheet survived for less than 14 days, and numerous microglia and macrophages were observed within and adjacent to the sheet. Here, we examined the roles of microglia and macrophages as well as acquired antibodies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Due to a decline in M1 markers and a raise in M2 markers, paracrine signaling of hMSC altered the microglial phenotype and the production of anti-inflammatory proteins in the retina ( 164 ). In neurological studies, MSCs have been found to induce M2 polarization in macrophages and facilitate their migration into MSCs in vitro ( 165 ). Therefore, it is conceivable that injecting MSCs into the vitreous cavity may be a potential therapeutic approach for treating DR since it may increase the number of microglia with anti-inflammatory phenotypes and help preserve the retina.…”
Section: New Strategies For Dr Treatment Targeting Polarizationmentioning
confidence: 99%
“…Due to a decline in M1 markers and a raise in M2 markers, paracrine signaling of hMSC altered the microglial phenotype and the production of anti-inflammatory proteins in the retina ( 164 ). In neurological studies, MSCs have been found to induce M2 polarization in macrophages and facilitate their migration into MSCs in vitro ( 165 ). Therefore, it is conceivable that injecting MSCs into the vitreous cavity may be a potential therapeutic approach for treating DR since it may increase the number of microglia with anti-inflammatory phenotypes and help preserve the retina.…”
Section: New Strategies For Dr Treatment Targeting Polarizationmentioning
confidence: 99%